Rapid measurement of meat spoilage using fluorescence spectroscopy - Wu, Binlin; Dahlberg, Kevin; Gao, Xin; Smith, Jason; Bailin, Jacob (Imaging, Manipulation, and Analysis of Biomolecules, Cells, and Tissues XV, 2017)
Food spoilage is mainly caused by microorganisms, such as bacteria. In this study, we measure the autofluorescence in meat samples longitudinally over a week in an attempt to develop a method to rapidly detect meat spoilage using fluorescence spectroscopy. Meat food is a biological tissue, which contains intrinsic fluorophores, such as tryptophan, collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) etc. As meat spoils, it undergoes various morphological and chemical changes. The concentrations of the native fluorophores present in a sample may change. In particular, the changes in NADH and FAD are associated with microbial metabolism, which is the most important process of the bacteria in food spoilage. Such changes may be revealed by fluorescence spectroscopy and used to indicate the status of meat spoilage. Therefore, such native fluorophores may be unique, reliable and nonsubjective indicators for detection of spoiled meat. The results of the study show that the relative concentrations of all above fluorophores change as the meat samples kept in room temperature (~19° C) spoil. The changes become more rapidly after about two days. For the meat samples kept in a freezer (~-12° C), the changes are much less or even unnoticeable over a-week-long storage.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/026-929-135-501-547, pop00136 tex.type: [object Object]
Keywords: Amino acids; Bacteria; Biological tissues; Biomolecules; Collagen; Flavin adenine dinucleotide; Fluorescence; Fluorescence spectroscopy; Fluorophores; Food microbiology; Histology; Meat food; Meats; Metabolism; Microbial metabolism; Molecular biology; NADH; Nicotinamide adenine dinucleotides; Nucleotides; Physiology; Rapid measurement; Relative concentration; Spectrum analysis; Spoilage; Tissue; Tryptophan; dept.phy

A Rapid Method Based on Fluorescence Spectroscopy for Meat Spoilage Detection - Wu, Binlin; Dahlberg, Kevin; Gao, Xin; Smith, Jason; Bailin, Jacob (International Journal of High Speed Electronics and Systems, 2018)
Food spoilage is mainly caused by microorganisms, such as bacteria. In this study, we measure the autofluorescence in meat samples longitudinally over a week in an attempt to develop a method to rapidly detect meat spoilage using fluorescence spectroscopy. Meat food is a biological tissue, which contains intrinsic fluorophores, such as tryptophan, collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) etc. As meat spoils, it undergoes various morphological and chemical changes. The concentrations of the native fluorophores present in a sample may change. In particular, the changes in NADH and FAD are associated with microbial metabolism, which is the most important process of the bacteria in food spoilage. Such changes may be revealed by fluorescence spectroscopy and used to indicate the status of meat spoilage. Therefore, such native fluorophores may be unique, reliable and non-subjective indicators for detection of spoiled meat. The results of the study show that the relative concentrations of all above fluorophores change as the meat samples kept in room temperature (~19°C) spoil. The changes become more rapidly after about two days. For the meat samples kept in a freezer (~ -12°C), the changes are much less or even unnoticeable over a-week-long storage.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-150-261-026-674, pop00221 tex.type: [object Object]
Keywords: Amino acids; Autofluorescence; Bacteria; Biological tissues; Collagen; Flavin adenine dinucleotide; Fluorescence; Fluorescence spectroscopy; Fluorophores; Food microbiology; Meats; Metabolism; Microbial metabolism; NADH; Nicotinamide adenine dinucleotides; Nucleotides; Relative concentration; Spoilage; bacteria; collagen; dept.phy; fluorescence spectroscopy; meat food; microbial metabolism; peer-reviewed; tryptophan

Patterned deposition of nanoparticles using dip pen nanolithography for synthesis of carbon nanotubes - Dahlberg, Kevin; Woods, Kelly; Jenkins, Carol; Broadbridge, Christine; Schwendemann, Todd C (MRS Proceedings, 2015)
Ordered carbon nanotube (CNT) growth by deposition of nanoparticle catalysts using dip pen nanolithography (DPN) is presented. DPN is a direct write, tip based lithography technique capable of multi-component deposition of a wide range of materials with nanometer precision. A Nanolnk NLP 2000 is used to pattern different catalytic nanoparticle solutions on various substrates. To generate a uniform pattern of nanoparticle clusters, various conditions need to be considered. These parameters include: the humidity in the vessel, temperature, and tip-surface dwell time. By patterning different nanoparticle solutions next to each other, identical growth conditions can be compared for different catalysts in a streamlined analysis process. Fe, Ni, and Co nanoparticle solutions patterned on silicon, mica, and graphite substrates serve as nucleation sites for CNT growth. The CNTs were synthesized by a chemical vapor deposition (CVD) reaction. Each nanoparticle patterned substrate is placed in a tube furnace held at 725°C during CNT growth. The carbon source used in the growth chamber is toluene. The toluene is injected at a rate of 5 mL/hr. Growth is observed for Fe and Ni nanoparticle patterns, but is lacking for the Co patterns. The results of these reactions provide important information regarding efficient and highly reproducible mechanisms for CNT growth. © 2015 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-622-015-549-684 tex.type: [object Object]
Keywords: Carbon nanotubes; Catalysts; Catalytic nanoparticle; Chemical vapor deposition; Chemical vapor depositions (CVD); Deposition; Dip-pen nanolithography; Lithography; Mica; Nanolithography; Nanoparticle catalysts; Nanoparticle clusters; Nanoparticle solutions; Nanoparticles; Nanotubes; Nickel; Patterned deposition; Patterned substrates; Silicate minerals; Substrates; Synthesis (chemical); Toluene; Vapor deposition; Yarn; dept.phy